Antihypertensive effects of oleuropein-enriched olive leaf extract in spontaneously hypertensive rats. Issue 1 (23rd November 2015) - Romero, M.; Toral, M.; Gómez-Guzmán, M.; Jiménez, R.; Galindo, P.; Sánchez, M.; Olivares, M.; Gálvez, J.; Duarte, J.
Abstract : The effects of chronic consumption of oleuropein-enriched (15% w/w) olive leaf extract (OLE) on blood pressure, endothelial function, and vascular oxidative and inflammatory status in spontaneously hypertensive rats (SHR) were evaluated. Abstract : The effects of chronic consumption of oleuropein-enriched (15% w/w) olive leaf extract (OLE) on blood pressure, endothelial function, and vascular oxidative and inflammatory status in spontaneously hypertensive rats (SHR) were evaluated. Ten Wistar Kyoto rats (WKY) and twenty SHR were randomly assigned to three groups: a control WKY group, a control SHR group and a SHR group treated with OLE (30 mg kg −1 ) for 5 weeks. Long-term administration of OLE reduced systolic blood pressure, heart rate, and cardiac and renal hypertrophy. OLE treatment reversed the impaired aortic endothelium-dependent relaxation to acetylcholine observed in SHR. OLE restored aortic eNOS phosphorylation at Ser-1177 and Thr-495 and increased eNOS activity. OLE eliminated the increased aortic superoxide levels, and reduced the elevated NADPH oxidase activity, as a result of reduced NOX-1 and NOX-2 mRNA levels in SHR. OLE reduced the enhanced vascular TLR4 expression by inhibition of mitogen-activated protein kinase (MAPK) signaling with the subsequent reduction of proinflammatory cytokines. In conclusion, OLE exerts antihypertensive effects on genetic hypertension related to the improvement of vascular function as a result of reduced pro-oxidative and pro-inflammatory status.